Implementasi Metode Multi Attribute Utility Theory pada Sistem Pendukung Keputusan dalam Pemilihan Siswa Unggulan - Nurhaliza, Rizky; Nurwati, Nurwati; Santoso, Santoso (Universitas Hamzanwadi, 2024)
Vocational School of Al Furqon is a private school that annually holds an election of excellent students. Vocational school Al Furqon selects excellent students manually so that the results of the assessment of superior students are less effective. The purpose of our research is to produce a decision-support information system for the selection of Excellent Students at Al-Furqon Batu Bara Vocational School by building a decision-support system using the Multi-Attribute Utility Theory (MAUT) method. The type of research used is quantitative. The research method used to develop this system is the waterfall method which starts from analysis, planning, implementation, and testing. In our research stages are interviews, observations, and literature studies. There are 70 alternatives but only 9 alternatives fall into the criteria, so only 9 alternatives are processed in the calculation. The subject and object of our research is the excellent student of Al Furqon Vocational School. The results of our research are presented in the form of a Decision Support System, the selection for superior students has been successfully implemented in the form of a website that can be accessed universally and anytime using the Internet with the results of the MAUT method calculation, Tantri Agustin Damanik got the highest score, namely with a total score of 1000 and was successfully named as an excellent student according to the calculation of the MAUT method and according to predetermined criteria.